Drivers of the eHealth transformation: beyond age and BMI - Niina Keränen; Pasi Pulkkinen; Timo Jämsä; Jarmo Reponen (Finnish Social and Health Informatics Association, 2013)
Purpose: To recognize the major trends driving development of connected healthcare devices in eHealth environment by 2030. Methods: Two phase search in commonly used open search engines. First we used regular Google search to find recent policy reports, consensus summaries and expert presentations. Then evidence regarding the recognized trends was sought using Google Scholar. Results: Statistics backing the often-cited trends of increasing cost of illness, potential for widening health inequality, and increasing need for health information exchange can be found. Conclusions: The focus of communication technologies in healthcare for connected devices should be on security in novel environments such as WBANs. However, the role of barriers of adoption may be greater than that of the drivers presented here.